The Influence of Serial Digital Image Media on Fable Text Writing Skills in Grade VII Students of Citayam Plus Middle School - Firdaus, Muhammad; Haryanti, Ade Siti; Permana, Adi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The aim of this research is to determine the effect of using serial digital image media on the skills of writing fable text in class VII students at SMP Citayam Plus. The research method used is an experimental method with a post-test only control group design. The population was 188 students, the number of samples used in the research was 60 students, using simple random sampling techniques, the instrument used in this research was an assessment sheet. The results of the research show that based on the results of the t test where 15.48 > 1.671 while ?ℎ????? > ??????, this means that there is an influence on the use of serial digital image media on the ability to write fable text in class VII Citayam Plus Junior High School students, because serial digital image media produces a higher average of 83.9 compared to the average value of learning outcomes that did not use serial digital image media of 63.80.